Pengaruh Hospitality Dan Lingkungan Kerja Terhadap Produktivitas Karyawan Di Puskesmas Penjaringan - Maria, Ana; Emita, Isyana (Journal of Comprehensive Science, 2025)
The purpose of this study is to examine the influence of Hospitality and Work Environment on Employee Productivity at Puskesmas Penjaringan. This research employed a quantitative approach with a population of 88 employees, from which a sample of 72 respondents was selected using purposive sampling techniques. Data were collected through questionnaires using a Likert scale, and the analysis was with the assistance of IBM SPSS Statistics 25 for Windows. The findings indicate that Hospitality has a positive and significant effect on employee productivity, as evidenced by a t-value of 4.335 > 1.994 with a significance level of 0.000 < 0.05. Similarly, the Work Environment variable also has a positive and significant effect on employee productivity, with a t-value of 6.998 > 1.994 and a significance level of 0.000 < 0.05. Simultaneously, Hospitality and Work Environment have a positive and significant impact on employee productivity at Puskesmas Penjaringan, as shown by an F-value of 29.808 > 3.980 with a significance level of 0.000 < 0.05. These results suggest that improvements in hospitality and work environment can significantly enhance employee productivity.